2012
DOI: 10.1111/j.1600-051x.2012.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

Refining definitions of periodontal disease and caries for prediction models of incident tooth loss

Abstract: Caries parameters best predicted incident tooth loss in men aged 20-39 years; in the intermediate and oldest age group and in young women, mean AL was most informative. Therefore, prediction models need to be developed for different age and gender groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…Our analysis revealed that the severity of atherosclerosis is linearly related to tooth loss, which often results from the breakdown of periodontal tissue caused by periodontal disease. As tooth loss is a marker of current and long-term cumulative effects of periodontal disease (Desvarieux et al 2003;Houshmand et al 2012), our findings suggest that periodontal disease may play a role in the pathogenesis of atherosclerosis progression. In this study, we excluded noninflammatory reasons for tooth loss such as traumatic or orthodontic procedures, because we considered that noninflammatory tooth loss may bias the association between tooth loss and CAVI.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our analysis revealed that the severity of atherosclerosis is linearly related to tooth loss, which often results from the breakdown of periodontal tissue caused by periodontal disease. As tooth loss is a marker of current and long-term cumulative effects of periodontal disease (Desvarieux et al 2003;Houshmand et al 2012), our findings suggest that periodontal disease may play a role in the pathogenesis of atherosclerosis progression. In this study, we excluded noninflammatory reasons for tooth loss such as traumatic or orthodontic procedures, because we considered that noninflammatory tooth loss may bias the association between tooth loss and CAVI.…”
Section: Discussionmentioning
confidence: 95%
“…Oral disease, such as periodontal disease, is characterized by chronic systemic inflammation and often results in tooth loss due to the breakdown of periodontal tissue. Therefore, tooth loss is a useful proxy for the accumulated burden of inflammatory disease (Desvarieux et al 2003;Houshmand et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that while there was no correlation between CCAP and periodontal bone loss, the number of teeth present was significantly higher in patients without CCAP (p-value<0.001). Periodontal disease as an etiology for tooth loss has been documented in the literature 51. The lack of correlation between periodontal bone loss and CCAP in our study could possibly be related to how periodontitis was defined, as other studies have primarily used clinical attachment loss and increased probing depth, while we used radiographic assessment only.…”
Section: Discussionmentioning
confidence: 79%
“…A study that compared several definitions of periodontal disease for predicting 5‐year tooth loss events suggested that prediction models need to be gender‐ and age‐specific, while mean CAL was the best definition to assess incident tooth loss. However, tooth loss and periodontal assessment in that study were restricted to half‐mouth examinations .…”
Section: Discussionmentioning
confidence: 99%
“…Healthy People 2020 includes a goal to reduce complete tooth loss by 10 percent (to 21.6 percent) among this age group . However, there are few models available to target interventions among individuals at high‐risk for tooth loss .…”
Section: Introductionmentioning
confidence: 99%